2021
DOI: 10.1080/23311916.2021.1968740
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of students’ comfort and adaptation in university dormitories in humid subtropical climatic area in winter in Chongqing, China

Abstract: Students' comfort and adaption in university dormitories is important for their learning. By controlling different environmental parameters (temperature, humidity, air velocity, etc.,) this can provide a great satisfaction in students' dormitory. In the present study, investigation was performed in students' dormitories in university in Chongqing, China. A survey was conducted on students' thermal comfort in typical university dormitories during winter in Chongqing, Southwest China. This also included on-site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Others have carried out satisfaction surveys on the types of university halls of residence that find favor with students [ 60 ]. One research direction includes surveys of the thermal comfort of university halls of residence [ 61 ]. Few studies, however, have examined how satisfied university students are with the indoor physical living environment of their halls of residence under regular epidemic prevention and control compared to before COVID-19.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Others have carried out satisfaction surveys on the types of university halls of residence that find favor with students [ 60 ]. One research direction includes surveys of the thermal comfort of university halls of residence [ 61 ]. Few studies, however, have examined how satisfied university students are with the indoor physical living environment of their halls of residence under regular epidemic prevention and control compared to before COVID-19.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By investigating foreign students in China, Li et al [ 16 ] found that foreign students have poor language foundation and lack of enthusiasm for learning. Additionally, they considered the school curriculum to be unreasonable, and yet were generally satisfied with school infrastructure [ 17 ].…”
Section: Introductionmentioning
confidence: 99%